2023
DOI: 10.1002/chem.202301086
|View full text |Cite
|
Sign up to set email alerts
|

Cover Feature: Facilitating [2+2] Photocycloadditions by Promoting Oxygen Tolerance and Substrate Activation in Water (Chem. Eur. J. 26/2023)

Abstract: Micellar photocatalysis allows for a simple and benign reaction set‐up using water as the solvent without the need for oxygen‐removing protocols. Blue light (456 nm) is absorbed by the photocatalyst and allows the [2+2] photocycloaddition to occur between α,β‐unsaturated carbonyl compounds and activated alkenes. The observed reactivity for α,β‐unsaturated aldehydes is completely turned on by the use of a micellar solution as opposed to organic solvents. More information can be found in the Research Article by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Using an aqueous sodium dodecyl sulfate (SDS) solution under green-light irradiation led to the desired ketone 2a in 62% NMR yield (Table 1, entry 1). Previous work from our group 25 showed that an oxygen sensitive photocycloaddition promoted by [Ru(bpy) 3 ] 2+ , which has been used as an oxygen sensor, 26 could be performed in micellar media without freeze-pump-thaw protocols. We hoped to observe similar effects in our protocol for a highly oxygen sensitive TTA-UC process, 27 and did not make any efforts to remove oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…Using an aqueous sodium dodecyl sulfate (SDS) solution under green-light irradiation led to the desired ketone 2a in 62% NMR yield (Table 1, entry 1). Previous work from our group 25 showed that an oxygen sensitive photocycloaddition promoted by [Ru(bpy) 3 ] 2+ , which has been used as an oxygen sensor, 26 could be performed in micellar media without freeze-pump-thaw protocols. We hoped to observe similar effects in our protocol for a highly oxygen sensitive TTA-UC process, 27 and did not make any efforts to remove oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…This further substantiates the idea that preassemblies form prior to oxidation, which are then bound more tightly upon oxidation which then alters the UV-vis and allows a catalytic reaction to take place. Such a finding reveals the critical role that solvents play in influencing outcomes of PRC reactions even in homogeneous solutions and not only micellular dispersions [25][26][27] and demands that solvent molecules are treated in experiments and calculations as an additional variable capable of tuning and not just as a spectator to the PRC reaction. Finally, our study highlights the added value of MD calculations in unravelling the mechanisms of PRC reactions that complements other theoretical approaches (QC) [28] and experimental approaches like isolation of authentic redox states.…”
Section: Resultsmentioning
confidence: 98%